2020
DOI: 10.46799/jsss.v1i3.33
|View full text |Cite
|
Sign up to set email alerts
|

Influence Competence And Placement of Employee On Employee Performance At PT. Xylo Indah Pratama in Musi Rawas Regency of Muara Beliti

Abstract: This research was conducted to determine the effect of employee competency and placement on employee performance at PT. Xylo Indah Pratama Muara Beliti Musi Rawas Regency. The results of this study indicate that there is a significant effect between Competency and Employee Placement on Employee Performance   Keywords : Competence, Employee placement, Employee performance

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 1 publication
0
1
0
1
Order By: Relevance
“…Selain penguasaan kompetensi yang unggul, placement (penempatan) karyawan sesuai dengan keahliannya juga berpengaruh pada kinerja karyawan maupun perusahaan. Penelitian (Khaerudin et al, 2018;Kurniawan et al, 2018;Mulyati & Utami, 2019;Ronal Aprianto et al, 2020) mengungkapkan bahwa strategi placement harus memperhatikan keahlian karyawan sehingga hal ini dapat meningkatkan kinerja perusahaan. Selain meningkatkan kinerja perusahaan, penempatan yang sesuai dengan kompetensi tersebut juga dapat meningkatkan prestasi kerja dan jenjang karir karyawan.…”
Section: Pendahuluanunclassified
“…Selain penguasaan kompetensi yang unggul, placement (penempatan) karyawan sesuai dengan keahliannya juga berpengaruh pada kinerja karyawan maupun perusahaan. Penelitian (Khaerudin et al, 2018;Kurniawan et al, 2018;Mulyati & Utami, 2019;Ronal Aprianto et al, 2020) mengungkapkan bahwa strategi placement harus memperhatikan keahlian karyawan sehingga hal ini dapat meningkatkan kinerja perusahaan. Selain meningkatkan kinerja perusahaan, penempatan yang sesuai dengan kompetensi tersebut juga dapat meningkatkan prestasi kerja dan jenjang karir karyawan.…”
Section: Pendahuluanunclassified
“…Thorytically the right placement has important effect on performance. Research found that the right placement has positive effect on employee performance (Ronal Aprianto et al, 2020) , In this company the placement process still does not match the interests and talents and experience of employees because the right placement in the right position will be able to assist the company in achieving the expected goals Elmi, (2018 : 53), Employee placement refers to assigning employees to certain jobs. This is particularly true for new hires and veteran workers who have held down roles that fal within the purview of the employee placement function in the sense of sustaining that function.…”
Section: Introductionmentioning
confidence: 99%